The Relationship Between Self-Compassion and Psychological Wellbeing of Students in Medan City - Siregar, Marsaulina; Simarmata, Nenny Ika Putri (CV Putra Publisher, 2026)
This study aims to determine the relationship between self-compassion and psychological well-being in students in Medan. Based on the results of the Pearson correlation test, it can be concluded that there is a strong positive relationship between self-compassion and psychological well-being in students who are writing a thesis. The higher the level of self-compassion, the higher the psychological well-being felt by students. The results of the categorization of psychological well-being based on aspects found aspects of self-acceptance (78.1%), positive relationships with others (82.2%), and autonomy (83%), indicating a good ability to accept oneself, establish healthy social relationships, and make decisions independently. In the aspects of environmental mastery, life goals, and personal growth, the distribution is more balanced between the medium and high categories, which indicates that some students still need to develop the ability to adapt to the environment, find clear life goals, and improve personal growth